2021
DOI: 10.1530/ec-21-0030
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of routine calcitonin measurement for the detection of medullary thyroid carcinoma in the management of patients with nodular thyroid disease: a meta-analysis

Abstract: Objective: The usefulness of routine calcitonin measurement for early detection of medullary thyroid carcinoma (MTC) in patients with nodular thyroid disease (NTD) has been investigated in various studies. Recently, a Cochrane review has been published on this issue, but a meta-analysis is lacking yet. Therefore, we performed this meta-analysis. Methods: We performed an electronic search using PubMed/Medline, Embase and the Cochrane Library. Studies assessing the diagnostic accuracy of routine calcitonin meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“… 11 These findings were supported with results from a recent meta-regression analysis. 13 However, Fugazzola et al 14 found that with using basal calcitonin cutoffs of >34 pg/mL for men and >30 pg/mL for women (area under curve 0.97 for men and 0.91 for women), the addition of calcium stimulation increased the sensitivity of MTC detection, particularly for patients with small MTC. In patients with thyroid nodular disease and basal calcitonin 10–100 pg/mL, stimulated calcitonin levels may be a useful adjunct to detect MTC and to facilitate appropriate initial surgery, although risks of potential overtreatment must be considered.…”
Section: Resultsmentioning
confidence: 99%
“… 11 These findings were supported with results from a recent meta-regression analysis. 13 However, Fugazzola et al 14 found that with using basal calcitonin cutoffs of >34 pg/mL for men and >30 pg/mL for women (area under curve 0.97 for men and 0.91 for women), the addition of calcium stimulation increased the sensitivity of MTC detection, particularly for patients with small MTC. In patients with thyroid nodular disease and basal calcitonin 10–100 pg/mL, stimulated calcitonin levels may be a useful adjunct to detect MTC and to facilitate appropriate initial surgery, although risks of potential overtreatment must be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with a slightly elevated bCt (between 10 and 100 ng/L) and nodular thyroid disease are those in whom diagnosing MTC (often a micro-MTC) is more challenging. In cases with Ct values in the grey zone, some authors suggest a wait-and-see strategy to avoid overtreatment ( 26 ). Alternatively, a calcium stimulation test could be performed in such cases, though some authors question the usefulness of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although the detection of MTC through routine calcitonin screening has recently been shown to lead to early stage diagnosis, the American Thyroid Association (ATA) guideline did not make recommendations for routine calcitonin measurement in nodular thyroid patients, leaving the decision up to the clinicians (13). However, many authorities recommend routine serum calcitonin measurement in nodular thyroid disease (4,9,10,17,19,20), but this recommendation is very controversial since it is considered that thyroid nodule prevalence is 33-68% (6,(21)(22)(23). In addition, the prevalence of MTC in nodular thyroid disease is unknown, and in thyroid cancers, its prevalence has been found to be 1-2% (1).…”
Section: Discussionmentioning
confidence: 99%